Ehlers–Danlos syndrome in a young woman with anorexia nervosa and complex somatic symptoms. Issue 3 (16th December 2017) - Lee, Michelle; Strand, Mattias
Abstract: The Ehler–Danlos syndromes (EDS) are a group of clinically heterogeneous connective tissue disorders characterized by joint hypermobility, hyperextensibility of the skin, and a general connective tissue fragility that can induce symptoms from multiple organ systems. We present a case of comorbid anorexia nervosa and EDS in a 23‐year old woman with a multitude of somatic symptoms that were initially attributed to the eating disorder but that were likely caused by the underlying EDS. Various EDS symptoms, such as gastrointestinal complaints, smell and taste abnormalities, and altered somatosensory awareness may resemble or mask an underlying eating disorder, and vice versa. Because of the large clinical heterogeneity, correctly identifying symptoms of EDS presents a challenge for clinicians, who should be aware of this group of underdiagnosed and potentially serious syndromes. The Beighton Hypermobility Score is an easily applicable screening instrument in assessing potential EDS in patients with joint hypermobility.